Use of Nitroglycerine Patch in the Management of Preterm Labor - Saima Umar, Sadia Anwar, Humaira Bashir, Muhammad Faizan, Qandeela Irum Qurashi, Umm-E-Aimen Saleem, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Preterm birth is the delivery of the baby before 37 completed weeks of pregnancy. The goal of tocolytic therapy is to reduce neonatal mortality and morbidity by delaying birth, allowing for corticosteroid administration and maternal transfer to the tertiary care center. This study was conducted to observe the tocolytic efficacy of GTN transdermal patches in preterm labor between 28 – 36 weeks of pregnancy. Methods: This cross-sectional study was done in Obstetrics & Gynecology Department at Mufti Mehmood Memorial Hospital, Dera Ismail Khan, from July 2017 to December 2017. Non-probability consecutive samplings of 186 pregnant women with preterm labor were included in the study. Detailed history and examination, routine investigations and ultrasound were performed to confirm viability, gestational age and exclusion of multiple pregnancies, lethal fetal malformation and intrauterine death. Effectiveness of the GTN patch was considered successful if the cessation of uterine contraction occurred within 24 hours of the application of the GTN patch and persisted for 48 hours to achieve the effect of steroids. Results: Tocolytic efficacy of GTN transdermal patch in preterm labor between 28 to 36 weeks of pregnancy was 88.71%. Regarding the parity of the women, 75.8% of women had multipara (parity 2 to 5) and 24.2% had primipara. The average gestational age was 33.15±2.28 weeks. . Two to three uterine contractions per 10 minutes were observed in 75.8% of women while four uterine contractions per 10 minutes were observed in 24.19% of cases. 2cm cervical dilatation was observed in 82 women (44.09%) and 3cm was 75 women (40.32%). Practical implication: The incidence of preterm delivery can be minimized using GTN patch to reduce the uterine contractions and increase the fetal viability inside the womb. Conclusion: There is no better incubator than a mother's womb. The GTN patch appears to be a safe, non-invasive method of suppressing uterine contractions in pre-term labor and also a simple, quicker and cost-effective tocolytic agent. Keywords: Pre-term labor; Tocolytic; Transdermal patch; Uterine contractions.